Preexisting Cerebral Abnormalities and Functional Outcomes After Acute Ischemic Stroke. (November 2019) - Qu, Jian-Feng; Chen, Yang-Kun; Zhong, Huo-Hua; Li, Wei; Lu, Zhi-Hao
Purpose: The aim of this study was to investigate the association between preexisting cerebral abnormalities in patients with acute ischemic stroke upon their functional outcomes. Methods: We recruited 272 patients with first-ever acute ischemic stroke. Cerebral abnormalities on magnetic resonance imaging included infarction, silent brain infarcts (SBI), enlarged perivascular spaces, white matter lesions (WMLs), global brain atrophy, and medial temporal lobe atrophy (MTLA). Functional outcomes were assessed using the instrumental activities of daily living (IADL) scale and basic activities of daily living (BADL) scale, at 3 and 6 months after the index stroke. Results: Two hundred and fifty patients completed the 3-month follow-up and 246 patients completed the 6-month follow-up. Univariate analyses showed that patients with poor IADL and BADL were older, more likely to be men, had higher National Institutes of Health Stroke Scale (NIHSS) score on admission, more frequent atrial fibrillation, and large artery atherosclerosis subtypes. They also had more frequent cortical infarcts, subcortical infarcts, infratentorial infarcts, larger infarct volume, more frequent presence of SBI, severe WMLs, and MTLA. In multiple regression analyses, NIHSS on admission, subcortical region infarct and MTLA were significant predictors of poor IADL at 3 months. National Institutes of Health Stroke Scale on admission, SBI and MTLA were significant predictors of poor IADL at 6 months. National Institutes of Health Stroke Scale on admission and MTLA were significant predictors of poor BADL at 3 months. National Institutes of Health Stroke Scale on admission and SBI were significant predictors of poor BADL at 6 months. Conclusions: In patients with acute ischemic stroke, the presence of SBI, and severe MTLA represent significant predictors of poorer functional outcomes, thus highlighting the importance of preexisting cerebral abnormalities.